HUBUNGAN TINGKAT STRES DAN FREKUENSI KONSUMSI FAST FOOD TERHADAP KEJADIAN DYSMENORRHEA PADA REMAJA SMK KESEHATAN FAHD ISLAMIC SCHOOL DI KABUPATEN BEKASI - Tasya Putri Iranti; Afrinia Eka Sari Sari (ARGIPA (Arsip Gizi dan Pangan), 2023)
The women who have experienced menstruation, there is a chance of dysmenorrhea. Dysmenorrhea tends to occur more frequently and more intensely, when accompanied by stressful conditions and having the habit of consuming fast food. This study aims to determine the relationship between stress levels and the frequency of fast food consumption on the incidence of dysmenorrhea. This research is a quantitative study with a cross-sectional design. The research sample are student of SMK Kesehatan Islamic School aged 15-17 years with a total of 260 respondents and used the consecutive sampling technique method. Based on the results of the analysis using the Chi-Square test, it was shown that the p-value = 0.008 (p<0.05) with an OR value (95% CI) = 2.308 for the relationship of stress levels with dysmenorrhea events and also obtained a p-value value = 0.001 (p<0.05) with an OR value (95% CI) = 3,933 for the relationship of the frequency of fast food consumption with the incidence of dysmenorrhea. The conclusion of this study is that there is a significant relationship between stress levels having 2.705 times chance and the frequency of fast food consumption having 3.600 times chance of the incidence of dysmenorrhea.